Building Intellectual Staff of Science – Technology Industrialization and Modernization Promotion in Vietnam: The Case of Vinh Long Province - Le Thi Hong Nhien (International Journal of Sustainable Applied Sciences, 2024)
In every era, intellectuals have always been the foundation of social progress, the core force of knowledge creation and dissemination. Today, along with the rapid development of science and technology, intellectuals have become a particularly important resource, creating the strength of each country in the development strategy. Accordingly, building and developing strong intellectual staff to meet the country's development requirements in the new context is a matter of both urgency and strategic importance. In Vietnam, our Party determines that building a team of intellectuals is a common responsibility of the whole political system and of the whole society, in which the Party and State play a decisive role. Thoroughly grasping the above viewpoint of the Party, in recent years, Vinh Long province has actively implemented the contents of the Party's guidelines, the State's policies and laws on building a contingent of intellectuals into practice to build a team of intellectuals in Vinh Long. In general, the work of building a team of intellectuals in general, and science-technology intellectuals in particular in Vinh Long has achieved very important results; However, besides the achieved results, there are still certain shortcomings and limitations that require further improvement of the system of regulations and policies to improve the quality of this team to meet the requirements of economic development socio-economic of the province in the coming time.